Regulation of phase separation and antiviral activity of Cactin by glycolytic enzyme PGK via phosphorylation in Drosophila. - Chen, D.; Shi, C.; Xu, W.; Rong, Q.; Wu, Q. (mBio, 2024)
Liquid-liquid phase separation (LLPS) plays a crucial role in various biological processes in eukaryotic organisms, including immune responses in mammals. However, the specific function of LLPS in immune responses in Drosophila melanogaster remains poorly understood. Cactin, a highly conserved protein in eukaryotes, is involved in a non-canonical signaling pathway associated with Nuclear factor-?B (NF-?B)-related pathways in Drosophila. In this study, we investigated the role of Cactin in LLPS and its implications for immune response modulation. We discovered that Cactin undergoes LLPS, forming droplet-like particles, primarily mediated by its intrinsically disordered region (IDR). Utilizing immunoprecipitation and mass spectrometry analysis, we identified two phosphorylation sites at serine residues 99 and 104 within the IDR1 domain of Cactin. Co-immunoprecipitation and mass spectrometry further revealed phosphoglycerate kinase (PGK) as a Cactin-interacting protein responsible for regulating its phosphorylation. Phosphorylation of Cactin by PGK induced a transition from stable aggregates to dynamic liquid droplets, enhancing its ability to interact with other components in the cellular environment. Overexpression of PGK inhibited Drosophila C virus (DCV) replication, while PGK knockdown increased replication. DCV infection also increased Cactin phosphorylation. We also found that phosphorylation enhances the antiviral ability of Cactin by promoting liquid-phase droplet formation. These findings demonstrate the role of Cactin-phase separation in regulating DCV replication and highlight the modulation of its antiviral function through phosphorylation, providing insights into the interplay between LLPS and antiviral defense mechanisms. Liquid-liquid phase separation (LLPS) plays an integral role in various biological processes in eukaryotic organisms. Although several studies have highlighted its crucial role in modulating immune responses in mammals, its function in immune responses in Drosophila melanogaster remains poorly understood. Our study investigated the role of Cactin in LLPS and its implications for immune response modulation. We identified that phosphoglycerate kinase (PGK), an essential enzyme in the glycolytic pathway, phosphorylates Cactin, facilitating its transition from a relatively stable aggregated state to a more dynamic liquid droplet phase during the phase separation process. This transformation allows Cactin to rapidly interact with other cellular components, enhancing its antiviral properties and ultimately inhibiting virus replication. These findings expand our understanding of the role of LLPS in the antiviral defense mechanism, shedding light on the intricate mechanisms underlying immune responses in D. melanogaster.